Development of Tie-Dye Technique on T-shirts in RT02 RW04 Sukawarna Village, Sukajadi District, Bandung - Lois Denissa; Rosa Permanasari; Cherish Rosethalia; Anjeli Tania; Vania Hindriana Ngo; Felicia Gunawan; Gerardine Nathania; Devina Theodora; Clemensy Aurelia (Journal of Innovation and Community Engagement, 2022)
Creativity is an essential thing that everyone needs to have so that life continues to be filled with constructive progress. The development of tie-dye technique is one of interesting textile design creativity because it is a synergistic experiment between technique and color. The application of the tie-dye technique on T-shirts as a form of community empowerment activity is considered to have power to stimulate ideas for developing the creativity of Islamic boarding school students in Sukawarna Village. The combination of various techniques such as tying, folding, sewing, wrinkling, and dyeing creates a natural and expressive movement of absorbent color that occurs permanently on the fabric. The participatory demonstration method which is directly applied to media by the participants with lecturers and students’ assistance becomes an effective method in producing interesting works. Participants have a rich visual repertoire of unexpected shapes and colors that can occur in fabrics while watching their friends explore. The conclusion of this creative experience becomes a force for students to be enthusiastic about continuing to work, until one day they have an opportunity to be self-sufficient. This unique result, if managed properly, will bring in consumers so that it can boost the family and even regional economy.